Interface Thermal Conductance of Nonequilibrium Thermal Transport across Nanoscale Metal Multilayers - Donghao Li; Zhongyin Zhang; Ziyang Wang; Gen Li; Jing Zhou; Jie Zhu; Dawei Tang (Advanced Devices & Instrumentation)
In the field of microelectronic device technology, the continuous miniaturization of components to nanoscale dimensions highlights the critical importance of thermal transport at metal/metal interfaces. In metallic materials, heat is transported by both electrons and phonons, leading to complex nonequilibrium coupled heat transfer processes, particularly on nanometer spatial and ultrashort temporal scales. However, conventional experimental characterizations of interface thermal conductance (ITC) often consider only equilibrium heat transport. This study compared ITC measurements at metal/metal interfaces using time-domain thermoreflectance (TDTR) under equilibrium and nonequilibrium conditions, modeled by Fourier’s law and the two-temperature model, respectively. The nanoscale Au/Cr multilayer samples were grown on various substrates, including sapphire, silicon, and silicon dioxide. These experiment results revealed that nonequilibrium ITC at the Au/Cr interface closely matched the predicted value of 6 GW m−2 K−1 by the electronic diffuse mismatch model, which captures ultrafast thermal behavior within the first few picoseconds following femtosecond laser heating. In contrast, equilibrium ITC values were an order of magnitude lower and exhibited significant substrate dependence. The study analyzed the physical differences between these 2 measurement approaches and demonstrated the superior accuracy and reduced substrate influence of nonequilibrium TDTR measurements for metal/metal multilayer structures.